Local Regulation on Homelessness and Beggars in Yogyakarta: Human Rights and Maqasid of Sharia Perspectives - Ahmad Syafii Rahman; Amir Mu’allim (Millah: Journal of Religious Studies, 2021)
The existence of vagrants and beggars as a sub-culture of poverty is a separate problem for the government and the people of Yogyakarta in general. This research was conducted to examine and analyze the effectiveness of the Yogyakarta City Government Regional Regulation No. 1 of 2014 concerning the handling of homeless and human rights beggars in the review of maqasid shariah and seeks to find the crucial factors that influence the effectiveness of the DIY city government regulation based on a human rights perspective. humans in the view of maqasid syariah. The facts in the field were collected using qualitative methods with a sociological normative juridical approach and technical analysis using analytical descriptions. The results of this study are the Role and Functions of the Social Service in tackling Homeless and Beggars in the Special Region of Yogyakarta which has been procedurally fulfilled based on the Yogyakarta Regional Regulation No. 1 of 2014, but conceptually has not been fully implemented in the DIY City Regional Regulation No. 1 of 2014. In the perspective of human rights, in terms of quantity, the regional regulation has guaranteed the fulfillment of the rights of the homeless and beggars, the implementation is in accordance with standard operational procedures in the field. According to the Maqasid syariah perspective, the government's program to overcome sprawl has realized the maqasid syariah, namely the maintenance of religion (hifz din), reason (hifz al-aql) maintenance of the soul (hifz al-nafs) maintenance of offspring (hifz al-nasl) maintenance of property ( hifz al-mal)